Effectiveness of empower-grief for relatives of palliative care patients: Protocol for an exploratory randomized controlled trial. - Neto, David Dias (2025)
Background: Grief reactions of relatives of palliative care patients are seldom addressed. Most interventions focus on Prolonged Grief Disorder (PGD) and not on its prevention. This is particularly relevant in palliative care, in which death is the result of a difficult period of a terminal illness, making caregivers particularly vulnerable to psychological distress. The purpose of the present exploratory trial is to test the efficacy of a selective intervention (Empower-Grief) for the initial problematic grief reactions and to study potential predictors of adherence and efficacy. Method: This is an exploratory Randomized Controlled Trial (RCT) studying Empower-Grief compared with Treatment as Usual (TAU). Participants will be relatives or caregivers of palliative and oncological patients with initial indicators of risk of developing PGD and will be randomly allocated to Empower-Grief and TAU. Participants will be assessed prior, at the end and six months after the intervention. The primary outcome considered will be symptoms of PGD. The assessment includes measures of anxiety and depression, coping, attachment, psychological flexibility, posttraumatic growth, social support and therapeutic alliance. Results: The trial is ongoing. Forty-four participants will be invited to participate. Conclusion: This study addresses the need for the development of empirically grounded and feasible interventions aimed at dealing with initial problematic reactions in grief, exploring potential predictors and possible venues for personalizing intervention and understanding the mechanism through which these interventions operate.